Grains of Trust: Nurturing Repurchase Intentions With Expertise and Likeability in Rice Sales - Kevin Gusriandi (PT. BERBAGI TEKNOLOGI SEMESTA, 2023)
This study examines the influence of salesperson likeability and expertise on repurchase intention within the framework of small and medium-sized enterprises (SMEs). In the highly competitive SME market, likeability—which goes beyond basic customer service to encompass qualities like relatability and empathy—has become a critical differentiation. Repurchase intention, which denotes consumer happiness and loyalty, is essential to the profitability and expansion of SMEs. The purpose of the study is to ascertain how salesperson expertise and likeability relate to repurchase intention. Using an online survey questionnaire, a sample of Padang, West Sumatera, clients of Beras Charissa is used in this quantitative study. The findings show that likeability and expertise both significantly influence the intention to repurchase. The study emphasizes how crucial likeability-based emotional ties and personal ties are in shaping consumer attitudes and actions. Furthermore, a salesperson’s expertise gives clients confidence, which improves trust and the customer experience. Although skill is still important, the article makes the case that improving a salesperson’s likeability through training that emphasizes customer engagement can boost client loyalty and promote repeat purchase.